The Libyan Sahara in the New Migratory Configurations - (:unkn) unknown (My University, 2000)
Traditionally a country of immigration where nationals from the rest of the Arab world come to work, Libya is becoming more and more attractive to migrants from sub-Saharan Africa. The pan-Africanism advocated by the regime of Mouammar Kadhafi explains, in part, this initial movement toward change in migratory patterns. At the same time, this question seems to affect to the entire North African Sahara. A spatial organisation based on intensified trans-national mobility is taking shape in the central Sahara, at the midpoint between West Africa and the North African coast. This spatial organisation is similar to that already found along other coastlines (specifically the north Moroccan coast) and among the Mediterranean islands. The flow of people (migrants, refugees, nomads) and of merchandise connects them to « cities of the State » beyond borders. Within the limits of the Sahara, this space is constructed through time, as it is dependent upon the relations maintained by different societies dispersed around different states. Beyond this, and whenever the political situation permits, this space integrates itself into more extended networks and incorporates the flow of migrants who aim to pursue their itinerary into the North African states and even into Europe. However, restrictions of movement often lead these migrants to stay in the Sahara, supposedly spaces of transit, transforming these spaces into migratory destinations « by default ». In this manner, the towns and villages of southern Libya are changing, producing an extension of informal settlements, the emergence of spaces for commerce and cosmopolitanism tied to the diversity of the populations present in these supposed « Saharan confines ».
Keywords: African Research